Is environmental degradation linked to transaction cost in Sub-Saharan Africa? - Salim, Ngnemadon Ahmed Ali; Xavera, Guedie Bogning Rolly; Ricado, Tchinda Kengne; Paul, Ningaye; Christian, Nzomo Tcheunta Joseph (Energy Economics Letters, 2023)
This research article aimed to examine the significance of transaction costs on CO2 emissions intensity in Sub-Saharan Africa (SSA) from 2003-2018. Based on a sample size of 33 countries, we specified models where the level of carbon pollution was directly linked to an increase in transaction rates. We then used the augmented STIRPAT model which accounts for changes in populations, wealths and technologies on environmental conditions. The system Generalized Method of Moments (GMM) framework is used as it accounts for the possible endogeneity arising from the reverse causality between the dependent and independent variables and the potential correlation between the error term and the country fixed-effects. The results based on this system GMM were conclusive; transactions cost has a persistent and strong negative effect on the country’s levels of greenhouse gas emissions. Transaction costs are one key reason why there is such variation between different forms of carbon dioxide intensities within SSA nations, specifically because they had been experiencing higher levels than other regions. An additional test reveals the existence of one of the most fundamental assumptions of environmental studies, namely the Environmental Kuznets Curve (EKC). As policy implications, it is recommended that authorities set up property rights as well as an emission permit market to solve environmental externalities.